Yoga and Eating Disorders: Can Mindful Movement Restore Balance? - Agopsowicz, Katarzyna; Blicharz, Katarzyna; Piwowar, Michalina; Biernacka, Martyna; Biernacki, Igor (Quality in Sport, 2025)
Eating disorders constitute a significant mental health issue, marked by serious disruptions in eating behaviors, body image concerns, and self-perception struggles. Individuals affected frequently endure substantial psychological and physical impacts, highlighting the need for comprehensive, multi-faceted treatment approaches. This article investigates yoga as an adjunctive therapeutic practice, focusing on mindful movement's capacity to enhance self-awareness, emotional stability, and promote a healthier relationship with one's body. Yoga encompasses physical poses, breathing techniques, and mindfulness strategies designed to cultivate greater body awareness and emotional connection. Engaging in mindful movement practices may enable those experiencing eating disorders to develop compassionate self-perception, reducing negative thought patterns and harmful behaviors. The article reviews existing research and expert perspectives regarding yoga's effectiveness in managing emotional dysregulation, alleviating anxiety and depressive symptoms, and improving overall psychological health in individuals dealing with eating disorders. Additionally, it offers practical guidance on integrating yoga into treatment protocols, outlining key considerations to ensure safety and efficacy. The aim is to provide valuable insights into yoga’s role in supporting recovery and fostering balance for individuals coping with eating disorders.